Baixa prevalência de não resposta virológica no resgate antirretroviral e fatores associados em uma coorte de pacientes vivendo com HIV-1 com falha virológica e resistência a múltiplos antirretrovirais - Sachetti, Rachel Juliana [UNIFESP] (2019)
Introduction: The treatment of patients with antiretroviral resistance, involving the association of potent drugs with high genetic barrier is very effective. However, rescue therapies have been poorly studied in routine clinical care, outside the conditions of a randomized trial, especially in low- and middleincome countries. In this study, we evaluated factors associated with virological non-response in patients with antiretroviral resistance following rescue therapy. Objective: The primary objective was to analyze the rate of nonresponse to antiretroviral treatment in multi-experienced antiretroviral patients receiving rescue regimen. Factors associated with virological nonresponse were evaluated, comparing those with responders to the rescue scheme with nonresponding patients. Methodology: Retrospective cross-sectional analysis of medical records of multi-experienced patients undergoing antiretroviral rescue treatment at an Infectious Disease Day Clínic in the city of São Paulo, Brazil. Rescue treatment responders were those patients who had an undetectable viral load within 24 weeks of introduction of the antiretroviral rescue regimen. Resistance analysis was based on genotyping test. Those who, after 24 weeks of adherence, did not and who never presented undetectable viral load were considered nonresponders. Factors analyzed for non-response were: sex, age, viral load and LTCD4+ at the beginning of the treatment, time of viral load negativity among responders, associated comorbidities, previous opportunistic infections, antiretroviral history, number of active drugs in the regimen and use of new classes. Statistical analysis: Data were entered into Excel and analyzed using STATA statistical software version 13.0 (StataCorp LP, CollegeStation, Texas, USA). Results: In this study, 140 multi-experimented patients were analyzed from July 2008 to March 2016. At baseline, LTCD4+ greater than 200 cells / mm3 was observed in 52.1% of patients and viral load below 100,000 copies / mL (50.7%). The mean number of previous failures was 5 (1-12 failures), with an average of 159 months from diagnosis of HIV infection. Upon rescue, approximately half of the patients received 3 or 4 active medications. One hundred and twelve patients (80.0%) used new classes. One hundred and thirty one (93.5%) were considered responders to rescue treatment. The average response time was 6.7 months.xviii Nine patients continued with detectable viral load after salvage treatment (Prevalence: 6.4%; [95% CI 3.0 - 11.9]). In the bivariate analysis, the factors significantly associated with non-response, were: alcoholism (p = 0.048), less than two rescue active drugs (p = 0.007) and LT CD4 + less than 200 prior to rescue (p = 0.017). In the multiple logistic regression analysis, it was observed that LTCD4 + less than 200 cells / mm3 prior to the rescue treatment, and the use of less than two active drugs in ARV rescue was independently associated with virologic non-response. Conclusion: Multidrug-resistant patients with antiretroviral resistance who underwent rescue therapy had a high virologic response rate, with CD4 + LT less than 200 cells / mm3 prior to rescue and use of less than two active drugs were independently associated with treatment failure.